The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/etc.4757
|View full text |Cite
|
Sign up to set email alerts
|

Application of Biomarker Tools Using Bivalve Models Toward the Development of Adverse Outcome Pathways for Contaminants of Emerging Concern

Abstract: As contaminant exposures in aquatic ecosystems continue to increase, the need for streamlining research efforts in environmental toxicology using predictive frameworks also grows. One such framework is the adverse outcome pathway (AOP). An AOP framework organizes and utilizes toxicological information to connect measurable molecular endpoints to an adverse outcome of regulatory relevance via a series of events at different levels of biological organization. Molecular endpoints or biomarkers are essential to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 143 publications
0
4
0
Order By: Relevance
“…These interlinked pathways can be assembled into AOPs and serve as a foundation for the development of a mechanistic understanding of toxicity and disease. Therefore, AOPs play an essential role in the ecological risk assessment of environmental contaminants (Ankley et al, 2010;Khan et al, 2020).…”
Section: Adverse Outcome Pathways-gaps In Terms Of Ecotoxicity and Nmsmentioning
confidence: 99%
“…These interlinked pathways can be assembled into AOPs and serve as a foundation for the development of a mechanistic understanding of toxicity and disease. Therefore, AOPs play an essential role in the ecological risk assessment of environmental contaminants (Ankley et al, 2010;Khan et al, 2020).…”
Section: Adverse Outcome Pathways-gaps In Terms Of Ecotoxicity and Nmsmentioning
confidence: 99%
“…Using the AOP framework, Khan et al (2020) showed that early events on molecular levels can be connected to important effects on bivalves organisms, which can be used as relevant biomarkers for the assessment of environmental risk related to the presence of contaminants of emerging concern [16].…”
Section: Examples Of Aop Uses In Studies Of Biomarkersmentioning
confidence: 99%
“…Therefore, it may be a valuable early toxicological warning signal to recognize and identify biomarkers before those irreversible abnormalities. Molecular biomarkers, such as DNA methylation, histone modification, chromatin remodeling, and noncoding RNA related to epigenetic methods, have received widespread attention as early warning indicators of pollutant exposure. , Among these factors, DNA methylation can change the homeostasis of the genome, leading to conformational changes in chromatin DNA, alterations in DNA stability, and the abnormal expression of structural and functional proteins. These changes will cause normal cell cycle inhibition, abnormal differentiation, and cell apoptosis. , To date, environmental contaminants, including trace elements, persistent organic pollutants (POPs), and endocrine disruptors (EDCs) have been found to induce DNA methylation via in vitro and in vivo assays. , These results indicate that DNA methylation may be an important biomarker of environmental chemical exposure and consequent changes to the aquatic ecosystem. …”
Section: Introductionmentioning
confidence: 99%
“…Molecular biomarkers, such as DNA methylation, histone modification, chromatin remodeling, and noncoding RNA related to epigenetic methods, have received widespread attention as early warning indicators of pollutant exposure. 16,17 Among these factors, DNA methylation can change the homeostasis of the genome, leading to conformational changes in chromatin DNA, alterations in DNA stability, and the abnormal expression of structural and functional proteins. These changes will cause normal cell cycle inhibition, abnormal differentiation, and cell apoptosis.…”
Section: ■ Introductionmentioning
confidence: 99%